Macroeconomic Consequences of global endogenous migration: A general equilibrium analysis - Vladimir Borgy; Xavier Chojnicki; Gilles Le Garrec; Cyrille Schwellnus (Center for Social and Economic Research (CASE), 2009)
In this paper, we analyze the demographic and economic consequences of endogenous migrations flows over the coming decades in a multi-regions overlapping generations general equilibrium model (INGENUE 2) in which the world is divided in ten regions. Our analysis offers a global perspective on the consequences of international migration flows. The value-added of the INGENUE 2 model is that it enables us to analyze the effects of international migration on both the destination and the origin regions. A further innovation of our analysis is that international migration is treated as endogenous. In a first step, we estimate the determinants of migration in an econometric model. We show, in particular, that the income differential is one of the key variables explaining migration flows. In a second step, we endogenize migration flows in the INGENUE 2 model. In order to do so, we use the econometrically estimated relationships between demographic and income developments in the INGENUE model, which enables us to project long-run migration flows and to improve on projections of purely demographic models.
Keywords: F21; C68; J61; H55; 330; CGEM; Migration; International capital flows; Internationale Migration; Wirkungsanalyse; Kapitalmobilität; Overlapping Generations; Theorie